2011
DOI: 10.5194/nhess-11-401-2011
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble analysis of frost damage on vegetation caused by spring backlashes in a warmer Europe

Abstract: Abstract. Tree dehardening and budburst will occur earlier in a warmer climate, and this could lead to an increased risk of frost damage caused by temperature backlashes. By using a spring backlash index and a cold hardiness model, we assessed different aspects of risk for frost damage in Norway spruce forests during the present climate and for one future emission scenario. Uncertainties associated with climate modelling were quantified by using temperature data from three climate data sets: (1) E-Obs gridded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The results of this study indicated that the temporal differences in timing of budburst between early and late provenances will remain in a warmer climate; however, the magnitude of temperature change will influence the regions and provenances most at risk. This is due to the fine balance between warmer climate generally reducing the number of frost days and tree dehardening and budburst occurring earlier in the year, at a time when temperature backlashes are more frequent (Jönsson & Bärring, ). While it was beyond the scope of this study to assess the risk of frost damage, it pointed toward the need of analyzing both the general trend in timing of budburst (most pronounced in northern Europe) and the interannual variation (will increase most in western Europe), as both aspects influence the risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study indicated that the temporal differences in timing of budburst between early and late provenances will remain in a warmer climate; however, the magnitude of temperature change will influence the regions and provenances most at risk. This is due to the fine balance between warmer climate generally reducing the number of frost days and tree dehardening and budburst occurring earlier in the year, at a time when temperature backlashes are more frequent (Jönsson & Bärring, ). While it was beyond the scope of this study to assess the risk of frost damage, it pointed toward the need of analyzing both the general trend in timing of budburst (most pronounced in northern Europe) and the interannual variation (will increase most in western Europe), as both aspects influence the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Potential implications that may follow from phenological shifts in trees include longer growing seasons, which may increase forest productivity (Richardson et al, 2010). However, as frost hardiness in spring is negatively related to growth activity (Westin, Sundblad, Strand, & Hällgren, 2000), an earlier onset of the growing season may increase the risks and severity of frost damage during late spring cold spells (Jönsson & Bärring, 2011). For commercially important species like Norway spruce, for which large differences in phenology traits exist among provenances, comprehensive cultivation research is carried out to identify traits favorable in a warmer climate (e.g., Skrøppa & Steffenrem, 2016;Westin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There is a risk that some regions are likely to experience severe reductions in available winter chill, potentially preventing endodormancy release in some perennials (Luedeling et al 2011). Early onset of spring phenology can increase the risk of tissue damage by subsequent frosts, the likelihood of which is typically high during the early spring (Saxe et al 2001, Jönsson and Bärring 2011).…”
Section: Climate Change and Damentioning
confidence: 99%
“…Variations in minimum air temperature, length of the frost-free season (FFS), as well as the timing of frost events are not reflected in a simple analysis of main climate elements (Robeson, 2002;Jönsson and Bärring, 2011). All three characteristics are economically important, and are studied extensively in Europe and throughout the world (Robeson, 2002;Fernández-Long et al, 2013;Winkler et al, 2013;Yu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%